SCREENING OF F2 POPULATION OF RICE FOR BACTERIAL BLIGHT IN RICE (Oryza sativa L.) - C. ANJALI; R.M. SUNDARAM, G. NAGAMANI, K.N. YAMINI, CH.V. DURGA RANI, G.S. LAHA (The Journal of Research, PJTSAU, 2023)
The bacterial blight of rice caused by Xanthomonas oryzae pv. oryzae (Xoo) is one of the most destructive diseases of rice in Asia. The disease can cause 20 to 80 percent yield loss and is difficult to manage by other means effectively. Development of host plant resistance is the most effective means to control this disease. Present study is an effort towards development of durable bacterial blight resistant varieties with high yield and as part of this, crossing was attempted between parents, IBTGM14 (resistant to gall midge and bacterial blight) and YPB46, (a high yielding line), F1s were generated and confirmed. The F2 population was screened against the pathogen under field condition by artificial inoculation. Among the two hundred and ninety five F2 individual plants screened at College Farm, PJTSAU, during Rabi 2020-21, 82 plants were found to be resistant against bacterial blight. These resistant plants which can be forwarded to further generations and evaluated for yield performance in future.